Bile acid hydrazides: gelation, structural, physical and spectroscopic properties - Pore, Vandana S.; Agalave, Sandip G.; Pharande, Shrikant G.; Patil, Prashant A.; Kotmale, Amol S. (New Journal of Chemistry, 2015)
Synthesis and gelation properties of a series of novel bile acid hydrazides are presented. These compounds are found to undergo self-assembly leading to organogelation in certain organic solvents. Compound 1 was found to be the most ``effective'' gelator in this series. The properties of this gel have been thoroughly investigated by conventional methods typical for molecular gel studies. Sol gel transition temperature (T-g) of chloroform gels of compounds 1 and 3 was found to increase with increase in the chain length. Sol-gel transition was probed using the isothermal time test and results show that there is instantaneous increase in both the moduli after shear melting, which suggests that the kinetics of formation of the network was very fast. IR and NMR studies revealed hydrogen bonding between amidic carbonyl in the side chain and hydroxyl groups of cholic acid.